Efficient Lattice Method for Valuing of Options with Barrier in a Regime Switching Model. (3rd October 2016) - Han, Youngchul; Kim, Geonwoo
Abstract : We propose an efficient lattice method for valuation of options with barrier in a regime switching model. Specifically, we extend the trinomial tree method of Yuen and Yang (2010) by calculating the local average of prices near a node of the lattice. The proposed method reduces oscillations of the lattice method for pricing barrier options and improves the convergence speed. Finally, computational results for the valuation of options with barrier show that the proposed method with interpolation is more efficient than the other tree methods.